University Presidents and the Politicians - Sirluck, Ernest (Canadian Journal of Higher Education, 1977)
This commentary does not deal with politicians within the university or at the federal or municipal levels, limiting itself to persons, whether elected or appointed, in government office at the provincial level. In addition to the university's "primary " area of interaction with government (Universities Minister, Grants Commission, Premier), there is an important "secondary "area (for example, Health, Agriculture, Energy and Resources, Industry, Labour, etc.) where there must be co-operation but where differing responsibilities imply different objectives. Examples are given to show that on the government side there has in recent years been a diminishing concern to prevent such differences from becoming clashes. In the "primary " sector the direction in which the relationship has moved in recent years has been downward. Public reaction against the universities and disunity within them have combined to invite government infringement upon university autonomy and abridgement of commitments; examples are given. The reasons for the absence of public protest are analyzed. A general conclusion is that a university's relations with government reflect pri- marily the realities of power and influence of the moment.